ADDIE Developed Video Critic Media for Islamic Education Critical Thinking: Pengembangan Media Video Critic Berbasis ADDIE Untuk Berpikir Kritis Pendidikan Agama Islam - Muhammad Nasrullah Ramadhana; Mardianto Mardianto; Mahariah Mahariah (Academia Open, 2026)
General Background: Digital transformation in education requires instructional innovation that promotes active learning and higher-order thinking skills among students. Specific Background: In Islamic Religious Education (Pendidikan Agama Islam/PAI) at SMP Muhammadiyah 56 Binjai Timur, learning practices remain dominated by teacher-centered lectures and textbook use, which limits student engagement and the development of critical thinking skills. Knowledge Gap: Although video-based learning media have been widely studied, most previous research focuses on general cognitive outcomes and rarely develops structured Video Critic media specifically designed to foster critical thinking in PAI learning contexts. Aims: This study aims to develop a Video Critic learning media and examine its feasibility, practicality, and learning outcomes for strengthening students’ critical thinking in Islamic Religious Education. Results: Using a Research and Development approach with the ADDIE model (analysis, design, development, implementation, and evaluation), the media was validated by subject-matter and design experts and implemented with eighth-grade students. Expert validation indicated very high feasibility (97%–100%), while practicality testing through focus group discussion with school leaders, teachers, and students showed a high usability score (average 91.8%). Learning results demonstrated improvement in students’ performance, with mean scores increasing from 66 (pretest) to 84 (posttest) and a normalized gain score of 0.52 categorized as moderate. Novelty: The study provides a systematically designed Video Critic media integrated with contextual cases and critical questions within the ADDIE framework for Islamic Religious Education. Implications: The developed media offers an alternative instructional approach that supports active participation, contextual understanding, and structured development of critical thinking skills in secondary-level PAI learning. Highlights • Expert validation confirms high feasibility of the developed learning media based on content and design assessment.• Student learning outcomes increased from pretest to posttest with a moderate normalized gain score.• Classroom implementation encourages analytical discussion, argumentation, and active participation during lessons. Keywords Video Critic Learning Media; Critical Thinking Skills; Islamic Religious Education; ADDIE Development Model; Secondary School Students